Towards Habitat III: Confronting the disjuncture between global policy and local practice on Africa's 'challenge of slums'. (April 2016) - Croese, Sylvia; Cirolia, Liza Rose; Graham, Nick
Abstract: The 'challenge of slums' is a global challenge, but particularly acute in Sub-Saharan Africa where in 2001 71.9% of the urban population lived in slums. This article reviews the housing programmes of a selected number of African countries (Angola, Namibia, Ethiopia and South Africa) to argue that while until recently African shelter policies at least in name continued to be mostly in line with international enabling and participatory approaches to dealing with the challenge of slums, in practice mass scaled supply-driven approaches to housing provision are on the rise. The article situates this practice historically and seeks to provide insight into some of the perceptions and factors that have underpinned and enabled its emergence. While noting a number of shortcomings of this supply-driven approach, it concludes that with Habitat III on the horizon it is important to confront the disjuncture between global policy and local practice in African cities.